A comparative study of sodium dodecyl sulfate and freezing/thawing treatment on wheat starch: The role of water absorption. (5th June 2016) - Tao, Han; Wang, Pei; Zhang, Bao; Wu, Fengfeng; Jin, Zhengyu; Xu, Xueming
Highlights: Sodium dodecyl sulfate (SDS) removed the surface components from starch granules. Freezing treatment after SDS washing was applied to claim the role of water absorption. SDS + freezing starch featured rough surfaces and hollow structure with amylose leaching. SDS + freezing treatment increased gelatinization parameters and pasting viscosities. Bread made with SDS + freezing starch had lower specific volume and firmer crumb texture. Abstract: The effect of freezing on functionality of native and sodium dodecyl sulfate (SDS)-treated wheat starches was investigated, with the aim of understanding the role of water absorption during freezing process. SDS is one of most efficient detergents to remove non-starch components (such as proteins and lipids) for starches but does not cause any apparent damage on granular structure. Slow swelling could be converted to rapid swelling by SDS washing, indicating higher water absorption. Freezing process induced slight roughness on starch granules but the non-starch components content was little affected. Combined SDS + freezing treatment significantly decreased both amylose and proteins non-starch components contents, which was accompanied with high gelatinization temperatures, melting enthalpy, and pasting viscosities. A smaller bread specific volume was obtained from SDS + freezing-treated starches while the crumb firmness significantly increased ( p < 0.05). SDS mainly extracted the surface components from starch granules, leading to high water absorption and making granules sensitive to the freezing treatment.